Divergent kinase regulates membrane ultrastructure of the Toxoplasma parasitophorous vacuole - Beraki, Tsebaot (Proc Natl Acad Sci U S A, 2019)
Apicomplexan parasites replicate within a protective organelle, called the parasitophorous vacuole (PV). The Toxoplasma gondii PV is filled with a network of tubulated membranes, which are thought to facilitate trafficking of effectors and nutrients. Despite being critical to parasite virulence, there is scant mechanistic understanding of the network’s functions. Here, we identify the parasite-secreted kinase WNG1 (With-No-Gly-loop) as a critical regulator of tubular membrane biogenesis. WNG1 family members adopt an atypical protein kinase fold lacking the glycine rich ATP-binding loop that is required for catalysis in canonical kinases. Unexpectedly, we find that WNG1 is an active protein kinase that localizes to the PV lumen and phosphorylates PV-resident proteins, several of which are essential for the formation of a functional intravacuolar network. Moreover, we show that WNG1-dependent phosphorylation of these proteins is required for their membrane association, and thus their ability to tubulate membranes. Consequently, WNG1 knockout parasites have an aberrant PV membrane ultrastructure. Collectively, our results describe a unique family of Toxoplasma kinases and implicate phosphorylation of secreted proteins as a mechanism of regulating PV development during parasite infection.